Application of educational data mining in subject learning at university - Irina A. Kotiurova (RUDN Journal of Informatization in Education)
Problem statement. Digital technologies are being actively incorporated into all educational processes, in particular so-called “end-to-end technologies”, which among others include big data as a management tool within educational systems. However, the described examples of practical use of educational data analysis not for university management, but for specific subject teaching are yet limited. The aim of the study is to determine how big data can be applied to verify gaps in knowledge and learning progress and to adjust the educational track accordingly in the context of a particular university course. Methodology . The study was conducted at PetrSU utilizing the PACT (Petrozavodsk Annotated Corpus of Texts). PACT is a database that is continuously updated with students' texts in German. The texts are reviewed by experts who mark errors and assign a grade for the work. All information about mistakes is collected in a shared database, the visualization of which is accessible in the teacher's personal account. The paper presents charts and tables from this database and determines to what extent they can be used to analyze the progress of a particular student, a certain academic group or an entire course in the acquisition of a foreign language. Results . The feasibility of big data collection in the form of students' work in progress has been confirmed, which can then be effectively applied in teaching. The PACT linguistic corpus allows, on one side, to track progress in mastering individual topics and, on the other side, to verify gaps in students' knowledge and to adjust teaching methods to meet the needs. Conclusion . Digitalization of education can and should develop in the direction of creating databases that include students' works on various subjects. The prospects for the use of such big data technologies in the subject teaching are immense, so this area, currently underdeveloped due to various reasons, certainly deserves more attention from all participants of the system - from the ordinary teachers to researchers and managers responsible for the digital transformation of education.